Technological Pedagogical Content Knowledge (TPACK): investigating senior primary mathematics teachers' integration of technology in the classroom in Okahao educational circuit - Shikesho, Hilya Ndahambelela (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
The overwhelming advancement of ICT devices in the contemporary Namibian education system has led to their praise for supporting differentiated instruction, fostering collaboration, and engaging multiple intelligences in teaching and learning. Consequently, the compulsory incorporation of ICTs into the teaching and learning process becomes imperative across various fields of study, including Mathematics. However, the integration of technology-based teaching proves to be a complex and challenging issue, often considered a wicked problem. To explore this matter, a qualitative case study was conducted to investigate how Senior Primary Mathematics Teachers integrated technology to develop their TPACK. The study was conducted among the twenty-seven senior primary mathematics teachers in the Okahao educational circuit in the Omuasti region. The study utilized Vygotsky's (1978); Socio-cultural Theory, together with Mishra and Koehler (2006), and; the Technological Pedagogical Content Knowledge (TPACK) framework was used as a lens to analyse the data. The data were gathered through semi-structured questionnaires, semi-structured interviews, focus group interviews, and lesson observations. The study findings indicate that senior primary mathematics teachers utilize the available resources at their respective schools during their classroom instruction. The study further reveals that mathematics teachers exhibit a positive attitude toward the integration of technology. The study uncovers the intricate interplay between technological knowledge, pedagogical expertise, and content knowledge within the context of mathematics education. The findings reveal that while participants demonstrate a high level of proficiency in certain TPACK components such as CK, TK, PK, TPK, and PCK, they expressed a moderate level of expertise in TCK and TPCK. The study also identified challenges in TPACK development, particularly the need for subject specific technology training, lack of technological infrastructure, particularly advanced technology, as well as a deficiency in ICT knowledge. The importance of access to various technologies was emphasized, enabling teachers to seamlessly integrate technology into their practices and address diverse learning styles.
Keywords: Technological Pedagogical Content Knowledge; Cultural-historical activity theory; Educational technology; Mathematics -- Study and teaching (Primary) -- Namibia -- Okahao; Mediated learning experience; Social interaction